2021
DOI: 10.1016/j.gie.2020.07.062
|View full text |Cite
|
Sign up to set email alerts
|

Salvage endoscopic resection after definitive chemoradiotherapy for esophageal cancer: a Western experience

Abstract: Background and Aims: Definitive chemoradiotherapy (CRT) is increasingly used as a nonsurgical treatment for esophageal cancer. In Japanese studies, salvage endoscopic resection (ER) has emerged as a promising strategy for local failure after definitive CRT. We aimed to evaluate the safety and efficacy of salvage ER in a Western setting.Methods: Gastroenterologists from Europe and the United States were invited to submit their experience with salvage endoscopic submucosal dissection (ESD) or endoscopic mucosal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Particularly in the current era of enhanced surgical procedures in the salvage setting for EC, e.g. endoscopic resections [41], robotassisted minimally invasive esophagectomy [42], and the advantages of high volume expertise centers [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in the current era of enhanced surgical procedures in the salvage setting for EC, e.g. endoscopic resections [41], robotassisted minimally invasive esophagectomy [42], and the advantages of high volume expertise centers [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, Hattori et al reported the results of the first EMR performed as a salvage treatment for local recurrence after CRT in Japan [ 19 ]. Consequently, several studies have been conducted to examine the effectiveness and safety of salvage ER after CRT [ 20 22 ], it has been regarded as important to detect recurrence after CRT while tumor remains in the superficial layer. In our institution, patients treated with CRT underwent follow-up EGD and CAT scans every 4–6 months during the first 5 years after CRT.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, organ preservation appears desirable after CRT, and this study by Al-Kaabi et al 6 shows that in expert hands endoscopic resection can be a viable alternative, but one has to weigh the consideration of curative margins and concern for locoregional dissemination in the long term against that of the mortality and morbidity from surgery and esophagectomy. Unfortunately, this decision making remains unclear, and patient factors and institutional experience will need to ultimately guide decision making because prospective data are still difficult to collate and are lacking.…”
mentioning
confidence: 91%
“…In this cohort, a total of 13 patients (52%) experienced recurrence after salvage ER, of whom 11 (44%) had locoregional recurrence only and 2 had distant disease (8%; Table 3 of Al-Kaabi et al 6 ). The median time of salvage ER to the occurrence of locoregional or distant recurrence was 9.6 months (interquartile range, 4-29; range, 2-48).…”
mentioning
confidence: 97%
See 1 more Smart Citation